TINJAUAN YURIDIS TERHADAP TINDAK PIDANA KEKERASAN DALAM RUMAH TANGGA (STUDI PUTUSAN No. 85/Pid.Sus/PN GST) - Tiranti Sitepu, Maresha; Marito Sinabutar, Eni (UNES Law Review, 2023)
Acts of domestic violence are the infliction of verbal, physical or mental suffering beyond certain limits on other people who are in the same house, such as against spouses, or parents, and these acts of violence are carried out in the home which can cause physical and psychological harm, humiliation, or deprivation of freedom from one of the parties. From this background, a problem can be stated, namely: what factors cause the occurrence of criminal acts of domestic violence and how the considerations of the Gunungsitoli District Court judges in deciding cases of criminal acts of domestic violence with decision Number 85/Pid.Sus/2020/PN GST. With a juridical normative legal research study method, primary, secondary and tertiary data sources in order to obtain research sources. The results in the decision that has been determined are very unfair to the victim witness where the panel of judges wrongly determined the decision that tried case Number: 85/Pid.Sus/2020/PN GST. The Panel of Judges determined the law of the crime of "Persecution" as in article 351 paragraph 1 of the Criminal Code determined at the Gunungsitoli District Court level I B, which should be included in article 44 paragraph 1.